IL-1β pre-stimulation enhances the therapeutic effects of endometrial regenerative cells on experimental colitis - Dingding Yu; Yiming Zhao; Hongda Wang; Dejun Kong; Wang Jin; Yonghao Hu; Yafei Qin; Baoren Zhang; Xiang Li; Jingpeng Hao; Guangming Li; Hao Wang (Stem Cell Research & Therapy, 2021)
Abstract Background Ulcerative colitis (UC) is a chronic, relapsing, and non-specific inflammatory bowel disease, and the current treatment strategies were mainly used to relieve symptoms or for maintenance. Endometrial regenerative cells (ERCs) are mesenchymal-like stromal cells and have been demonstrated to alleviate multiple immune-dysregulation diseases. Pro-inflammatory stimuli were reported to enhance the immunosuppressive functions of ERCs, but the mechanism underlined is not fully understood. Here, we have designed this study to investigate the therapeutic effects of IL-1β-primed ERCs in the attenuation of experimental colitis. Methods BALB/c mice were given 3% dextran sodium sulfate (DSS) for 7 consecutive days and free tap water for 3 days sequentially to induce experimental colitis. PBS (200 μL), ERCs, and IL-1β-primed ERCs (10ng/mL, 48 h) were injected (1 million/mouse/day, i.v.) on day 2, 5, and 8, respectively. Colonic and splenic samples were harvested on day 10 after DSS induction. Results It was found that IL-1β-primed ERC treatment markedly attenuated colonic damage, body weight loss, and colon length shortening in colitis mice. Compared with other treatments, cell populations of CD4+IL-4+Th2 cells, CD4+CD25+FOXP3+ regulatory T cells (Tregs), and CD68+CD206+ macrophages in spleens were also significantly upregulated in the IL-1β-primed ERC-treated group (p < 0.05). In addition, lower expression of pro-inflammatory (IFN-γ, IL-17, TNF-α, and IL-6), but higher levels of anti-inflammatory cytokines (IL-4 and IL-10) were detected in colons in the IL-1β-primed ERC-treated group (p < 0.05 vs. other groups). Importantly, we also found that different generations of ERCs had an overall lower secretion of Dickkopf-1 (DKK1) by IL-1β pre-stimulation (p < 0.05) and a higher expression of β-catenin in colonic and splenic tissues after the administration of IL-1β-primed ERCs. Conclusions This study has demonstrated that IL-1β pre-stimulation effectively downregulated DKK1 expression in ERCs, which in turn promoted the wnt/β-catenin pathway activation in colonic and splenic tissues. Consequently, IL-1β-primed ERCs exhibited an enhanced therapeutic effect in the attenuation of DSS-induced colitis.